The biofilm formed by Pseudomonas species associated with plants. Two models: P. chlororaphis in the rhizosphere and P. syringae in the phyllosphere. - Heredia Ponce, Zaira María; Gutiérrez Barranquero, José Antonio; De-Vicente-Moreno, Antonio; Cazorla-López, Francisco Manuel (My University, 2018)
Pseudomonas syringae is a bacterium which produces diseases in aerial parts of both herbaceous and woody plants. Otherwise, Pseudomonas chlororaphis interacts with the plant rhizosphere and is a biocontrol agent of plant fungal diseases. Both these bacterial species form biofilms and, despite their different life style (epiphyte-pathogen and rhizosphere-biocontrol agent), they are closely related in phylogenetic analyses. We think that because of this relatedness, they must contain some common and different components in the biofilm matrix, which may basically reflect the different lifestyle that these bacteria have while interacting with their host. Analysis in silico have showed some common and different regions that may codify proteins as candidates for producing biofilm-matrix components. We have constructed mutants of these regions and analysed their implications in aspects related to biofilm formation. These regions may reflect the different lifestyle between these two-bacterial species.
Comunicación a congreso en forma de póster
Keywords: Pseudomonas; Biofilm; Aguacate; Mango